Different Targets of Monoclonal Antibodies in Neuromyelitis Optica Spectrum Disorders: A Meta-Analysis Evidenced From Randomized Controlled Trials - Xue, Tao; Yu, Jiahao; Chen, Shujun; Wang, Zilan; Yang, Yanbo; Chen, Zhouqing; Wang, Zhong (Frontiers in Neurology, 2020)
Abstract Background Neuromyelitis optica spectrum disorder (NMOSD), an autoimmune inflammatory disorder of central nervous system, often leads to vision loss or paralysis. This meta-analysis focused on the assessment of the monoclonal antibody therapy in NMOSD and compared different targets of monoclonal antibodies with each other in efficacy and safety outcomes. Method We searched through the databases of MEDLINE, EMBASE, Central Register of Controlled Trials (CENTRAL) and clinicaltrials.gov for the randomized controlled trials (RCTs) evaluating monoclonal antibody therapy in NMOSD. Results We identified seven randomized controlled trials (RCTs), including 775 patients (monoclonal antibody group, n = 485 and placebo group, n = 290). Monoclonal antibody therapy decreased relapse risk (RR 0.33, 95% CI 0.21 to 0.52, P<0.00001), annualized relapse rate (ARR) (mean -0.28, 95% CI −0.35 to −0.20, P<0.00001) , expanded disability status scale score (EDSS) (mean -0.19, 95% CI −0.32 to −0.07, P=0.002) and serious adverse events (RR 0.78, 95% CI 0.61 to 1.00, P=0.05). However, we did not observe any significant difference in terms of adverse events or mortality. Further, the subgroup analysis demonstrated that anti-complement protein C5 monoclonal antibody (eculizumab) might have lower relapse risk (RR 0.07, 95% CI 0.02 to 0.23, P<0.0001) in the AQP4 seropositive patients, and anti-interleukin-6 receptor monoclonal antibodies (satralizumab and tocilizumab) showed decreased EDSS score (mean -0.17, 95% CI -0.31 to -0.02, P = 0.02) more effectively than other monoclonal antibodies. Conclusions Monoclonal antibodies were effective and safe in NMOSD. Different targets of monoclonal antibodies might have their own advantages.